PENGARUH KINERJA KEUANGAN DAN CORPORATE GOVERNANCE TERHADAP HARGA PASAR SAHAM - Rizal Noviananda; Agung Juliarto (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of financial performance, and corporate governance on stock market prices. Financial performance is tested by the current ratio, debt to equity ratio, total asset turnover, and return on assets. Corporate governance is measured by the score of the Corporate Governance Perception Index (CGPI). This study uses secondary data in the form of company annual reports and market data available on Bloomberg and IDX. The population of this study are companies listed on the Indonesia Stock Exchange in 2015-2017 and samples from this study were selected using a purposive sampling method with the criteria of non-financial companies that are consistently included in LQ 45 and have the data needed in this study. There are 25 companies that meet the criteria as research samples. Data analysis was carried out by multiple linear regression analysis methods. The results showed that the current ratio and roa did not significantly influence stock prices. Meanwhile, corporate governance has a negative influence on the stock prices. In addition, the debt to equity ratio and total asset turnover have a positive influence on stock prices.